Simulation of PV solar coconut dehusking machine - Dominic Merikan, Bonny Jinggut (2016)
Solar PV coconut dehusking machine is one of the most important application of renewable energy especially in rural areas. It's not only improve the socio - economy in rural areas but reduce the risk of injuries while they dehusking the coconut manually. Thus the purpose of the study is to simulate the performance of the Solar PV coconut dehusking machine by circuit modeling in Simulink and PVsyst software. While the system is in a modeling and simulation of Simulink, simulation results show that it can match the rpm and torque of the dry coconut shear test. Fu1tbermore, its offer better cost of ownership in the long term if compare to the fossil fuel dehusking dependable machine based on PVsyst analysis.